microRNA-203 inhibits migration and invasion of canine tonsillar squamous cell carcinoma cells by targeting SLUG - Noguchi, Shunsuke; Matsui, Asuka (Frontiers in Veterinary Science, 2023)
Objective: Squamous cell carcinoma (SCC) occurring in the tonsils (TSCC) has a poorer prognosis than SCC occurring in other regions of the oral cavity (non-tonsillar SCC [NTSCC]) because it easily metastasizes to distant organs. This study aimed to elucidate the molecular mechanisms underlying the migration and invasion of TSCC cells in vitro. Materials and Methods: This study focused on differential microRNA (miRNA) expression using microRNA microarrays and quantitative polymerase chain reaction in canine TSCC and NTSCC tissues and cell lines. A target gene of the miRNA involved in cell migration and invasion was validated by wound healing, transwell, and luciferase assays. Results: miR-203 expression was lower in TSCC tissues than in the normal oral mucosa and NTSCC tissues. Transfection of the miR-203 mimic resulted in the downregulation of mesenchymal marker protein expression and attenuation of cell migration and invasion in TSCC cells, but not in NTSCC cells. A dual-luciferase assay revealed that miR-203 directly targeted the mesenchymal transcription factor SLUG. SLUG overexpression enhances the migration of TSCC cells. Conclusion: Our study indicates that the miR-203/SLUG axis may be involved in the metastatic mechanisms of TSCC.